Penerapan Metode Peta Konsep untuk Meningkatkan Prestasi Belajar Bahasa Indonesia Materi Jenis-Jenis Paragraf pada Siswa di MI Muhammadiyah Grubug, Kulon Progo - Suprapmi, Suprapmi (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
This study aims to identify improvements in student achievement through the application of the concept map method to subjects Indonesian Paragraph Types material. This study is class action research conducted in two cycles. The subjects of the study were grade VI students at MI Muhammadiyah Grubug. Research data includes learning achievement taken from giving test questions in each cycle, the results of interviews with students to provide input on the course of the research process. The results showed that the application of the concept map method can improve student achievement. In cycle I, the student achievement index was at the highest score of 82, and the lowest score of 69, increasing quite significantly in cycle II with the highest score of 92, and the lowest score of 72. The classical completeness criterion also increased significantly by 72% in cycle I to 100% in cycle II. The concept map method can be applied to students for Indonesian subjects.